Time Lapse Looped in Hollis Frampton's Remote Control - Powers, John (Discourse (Berkeley, Calif.), 2022)
It is surprising that Hollis Frampton's published writing contains no explicit reference to time-lapse cinematography.1 After all, Frampton straddled the disciplinary boundaries between science and art, claimed dual status as still photographer and filmmaker, and made movement and time central to his theoretical speculation, a cluster of investments that would seem, at the least, time-lapse adjacent. Moreover, some form of the technique appears in his films Surface Tension (1968), Ordinary Matter (1972), Pas de Trois (1975), and, the subject of this essay, Remote Control (1972). In this film, which occupies the sixth position in the seven-part Hapax Legomena, Frampton applies time lapse, a technique with phylogenetic roots in the natural sciences, to flatly inorganic subject matter: the television set.